Petrography and geochemistry of Ahwaz Sandstone Member of Asmari Formation, Zagros, Iran: implications on provenance and tectonic setting - Mahdi Jafarzadeh; Mahboobeh Hosseini-Barzi (Revista Mexicana de Ciencias Geológicas)
An integrated petrographic and geochemical study of the Ahwaz Sandstone Member of Oligocene- Miocene age, Asmari Formation in Zagros, southwest Iran, was carried out to infer their provenance and tectonic setting. This study is based on the analysis of core samples from three subsurface sections (wells Az-85, Az-11, and Az-89) in Ahwaz oil field in the Dezful embayment subzone.